Evaluation of antitumor effect of zoledronic acid entrapped in folate-linked liposome for targeting to tumor-associated macrophages. (June 2015) - Hattori, Yoshiyuki; Yamashita, Jun; Sakaida, Chisato; Kawano, Kumi; Yonemochi, Etsuo
Abstract In this study, we investigated the possibility of whether depletion of tumor-associated macrophages (TAMs) by zoledronic acid (ZOL) entrapped in folate-linked liposome could inhibit tumor angiogenesis and consequently tumor growth. Abundant expression of folate receptor β (FRβ) mRNA was detected in tumor tissues from subcutaneously implanted FR-negative tumor cells in mice, indicating that FRβ mRNA was expressed in TAMs, not in tumor cells. When fluorescent-labeled folic acid was intravenously injected into mice bearing FR-positive human nasopharyngeal tumor KB, and FR-negative human prostate tumor PC-3 and mouse colon adenocarcinoma Colon 26, fluorescence was strongly detected in KB and Colon 26 tumors, and moderately in PC-3 tumor, indicating that folic acid was taken up by TAMs via FRβ in PC-3 and Colon 26 tumors. For evaluation of ZOL delivery to TAMs, folate-linked liposomal ZOL (FL-ZOL) for TAM targeting and non-folate-linked liposomal ZOL (L-ZOL) as a control were prepared by incorporation with 0.5 mol% folate-PEG2000-DSPE and 0.5 mol% PEG2000-DSPE, respectively, into the liposomal formulation of egg phosphatidylcholine and cholesterol. FL-ZOL showed high cytotoxicity for KB and murine macrophage RAW264.7 cells, but not for Colon 26 cells, suggested that FL-ZOL was selectively taken up via FR-mediated endocytosis. However, injections of FL-ZOL and L-ZOL did not induce antitumor activities for KB and Colon 26 tumor-bearing mice, and had a lethal effect by high toxicity. From these findings, the severe in vivo toxicity of liposomal ZOL limited its utility for in vivo TAM targeting, although FL-ZOL could selectively induce in vitro cytotoxicity via FR.